2013
DOI: 10.1155/2013/260758
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Research of Splat Formation Process in Thermal Spraying

Abstract: Thermal spraying is a well-established surface modification technology which has been widely used in industrial applications. As the coating properties were mainly determined by the flattening nature of each splat, much attention has been increasingly paid to the study on the splat formation process of thermal sprayed particles. This paper is concerned with the development in the research of the splat formation process of the individual splat deposited by thermal spraying during the past few decades, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 109 publications
(198 reference statements)
0
8
0
1
Order By: Relevance
“…Since this work concentrates on the macro coating thickness profile (the radius of a single coating profile is typically several millimeters), the micro-level splat morphology (the radius of a single splat typically ranges from several micrometers to several hundred micrometers) is simplified with reasonable assumptions, which are discussed in the following paragraphs. Here the splat morphology [42] is the final shape of a single particle on the substrate or previously deposited coating layer after the impact, spreading, and solidification. In addition, according to the above major characteristics of the coating formation, some rules for calculating the pile-ups of particles are adapted in this work on the basis of previous related research works [2,8,28].…”
Section: The Coating Profile Based On the In-flight Behavior Model 321 Splat Morphology Approximation And Coating Growthmentioning
confidence: 99%
“…Since this work concentrates on the macro coating thickness profile (the radius of a single coating profile is typically several millimeters), the micro-level splat morphology (the radius of a single splat typically ranges from several micrometers to several hundred micrometers) is simplified with reasonable assumptions, which are discussed in the following paragraphs. Here the splat morphology [42] is the final shape of a single particle on the substrate or previously deposited coating layer after the impact, spreading, and solidification. In addition, according to the above major characteristics of the coating formation, some rules for calculating the pile-ups of particles are adapted in this work on the basis of previous related research works [2,8,28].…”
Section: The Coating Profile Based On the In-flight Behavior Model 321 Splat Morphology Approximation And Coating Growthmentioning
confidence: 99%
“…Fukumoto et al [34] studied how the fraction of disk-shaped splats varies with the substrate temperature for Ni particles sprayed on an AISI304 stainless steel substrate. Yang et al [28,36] studied the influence of low pressure on splat formation and found that by reducing the ambient pressure the splat shape changed to a disk-like one and the adhesion strength increased. Sakakibara et al [35] plasma-sprayed yttriastabilized zirconia particles on a polished stainless steel surface and confirmed that the transition to disk-like splats occurred at a substrate temperature of 150 to 200°C.…”
Section: Coating Microstructure and Adhesion Strengthmentioning
confidence: 99%
“…The deposition of particles during plasma spraying can only be poorly observed experimentally, due to the fact that splat formation and solidification occur within a few microseconds [4]. Consequently, many studies have been devoted to numerical and analytical investigation of particle impact, splat formation, and solidification [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%